Games For Teaching Grammar To Young Learners - nelvia ibrahim (Indonesian Journal of Integrated English Language Teaching, 2016)
Teaching grammar for beginner is not quite easy, but it is not difficult to teach. Young learners have their own way to accept a new knowledge and they will accept all of it by happiness. Teacher need to find good method and good media to teach grammar, and one of the effective methods is using games although children learn a language faster than adults, they do not learn through traditional language teaching methods. Through fun activities children can learn a language better as learning becomes natural for them since these activities do not make them conscious that they are learning a language.